2011
DOI: 10.1037/a0024330
|View full text |Cite
|
Sign up to set email alerts
|

Grouping and emergent features in vision: Toward a theory of basic Gestalts.

Abstract: Gestalt phenomena are often so powerful that mere demonstrations can confirm their existence, but Gestalts have proven hard to define and measure. Here we outline a theory of basic Gestalts (TBG) that defines Gestalts as emergent features (EFs). The logic relies on discovering wholes that are more discriminable than are the parts from which they are built. These wholes contain EFs that can act as basic features in human vision. As context is added to a visual stimulus, a hierarchy of EFs appears. Starting with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 49 publications
8
95
0
Order By: Relevance
“…A one-sample t-test (2-tailed) confirmed that the mean index was significantly greater than the prediction of optimal summation (t(3) = 3.32, p < .05). In fact, these data are consistent with recent results reported by Pomerantz and Portillo (2011) and Pomerantz and Cragin (2013) who found that co-linearity of line segments in a manner akin to our Vernier stimuli yielded stronger configural superiority effects than Kanisza-square stimuli defined by illusory contours.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…A one-sample t-test (2-tailed) confirmed that the mean index was significantly greater than the prediction of optimal summation (t(3) = 3.32, p < .05). In fact, these data are consistent with recent results reported by Pomerantz and Portillo (2011) and Pomerantz and Cragin (2013) who found that co-linearity of line segments in a manner akin to our Vernier stimuli yielded stronger configural superiority effects than Kanisza-square stimuli defined by illusory contours.…”
Section: Resultssupporting
confidence: 93%
“…For example, Sekuler and Palmer (1992) found that when observers were primed with a partly occluded version of an object, they were faster to make subsequent decisions about filled-in versions of the object than incomplete versions matching the stimulus they had seen previously. Similarly, Pomerantz and colleagues (Eidels, Townsend & Pomerantz, 2008; Pomerantz, 2003; Pomerantz & Portillo, 2011; Pomerantz & Pristach, 1989; Pomerantz, Sager & Stoever, 1977) have found that reaction times for discriminating amongst sets of items can be much faster when presented within the context of features that are entirely redundant but that elicit the percept of a perceptually complete figure (what they call the ‘configural superiority effect’). Ringach and Shapley (1996) have found that orienting the elements of a Kanisza figure so that observers no longer perceive illusory or occluded contours can result in dramatic decreases in discrimination accuracy.…”
Section: Introductionmentioning
confidence: 93%
“…Our results are in agreement with other paradigms in which wholes determine the appearance of parts (e.g., Hochstein & Ahissar, 2002;Pomerantz & Portillo, 2011;Weisstein & Harris, 1974;Wertheimer, 1923). We found that larger masks improve performance also in pattern and metacontrast masking (Duangudom, Francis, & Herzog, 2007;Herzog & Fahle, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…When the configuration induced by the context improved performance, it was called a configural-superiority e ect; when it negatively a ected performance, it was called a configural-inferiority e ect. Over the years, Pomerantz and colleagues (Pomerantz, 1983;Treisman & Paterson, 1984;Pomerantz & Portillo, 2011) have postulated a number of emergent features for lines and dots which could account for these results.…”
Section: Dotsmentioning
confidence: 99%
“…The properties of individual dots are DOTS Figure 1 . Example odd-quadrant stimuli adapted with permission from Pomerantz and Portillo (2011) subsumed by their overall organization, and the phenomenology is controlled by a small set of parameters (Kubovy & Gepshtein, 2003).…”
Section: Components or Configurations?mentioning
confidence: 99%